2003
DOI: 10.1007/bf02897918
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of indoor air pollution by chlorpyrifos: Determination of chlorpyrifos in indoor air and 3,5,6-trichloro-2-pyridinol in residents’ urine as an exposure index

Abstract: Objects: We carried out an investigation to clarify the real state of indoor air pollution by chlorpyrifos (termiticide) and exposure to chlorpyrifos of residents by measuring its urinary metabolite 3,5,6-trichloro-2-pyridinol (TCP) as an exposure index, such as biological monitoring.Methods: The investigation was conducted in 43 individual houses with termiticide application (whether the termiticide was chlorpyrifos is uncertain) and 3 control houses without any termiticide application in Kagawa, Japan. Urine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“… 33 Another study reported urinary TCP concentrations of 0.1–7.8 μ g/g creatinine in 41 residents from houses where chlorpyrifos had been detected in collected indoor air samples. 34 Alexander et al 35 reported a study of farm family members (spouses, and children aged 4–17 years) from Minnesota and South Carolina. Five consecutive 24-h urine samples were obtained from 34 families of licensed pesticide applicators from one day before to three days after a chlorpyrifos application.…”
Section: Discussionmentioning
confidence: 99%
“… 33 Another study reported urinary TCP concentrations of 0.1–7.8 μ g/g creatinine in 41 residents from houses where chlorpyrifos had been detected in collected indoor air samples. 34 Alexander et al 35 reported a study of farm family members (spouses, and children aged 4–17 years) from Minnesota and South Carolina. Five consecutive 24-h urine samples were obtained from 34 families of licensed pesticide applicators from one day before to three days after a chlorpyrifos application.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, 19 studies were selected. (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) The selections were based on the following criteria: (1) large-scale survey, for example, nationwide or prefecturewide; (2) random sampling (not a specific population, such as allergic subjects);…”
Section: Exposure Assessmentmentioning
confidence: 99%
“…Although the chambers contained a separate compartment for the ticks to hide and possibly escape the acaricide, it may be possible that after being forced to stay on the animal, the temptation of a blood meal was stronger than the repellent effect of the drug. On the other hand, it has been reported that permethrin is not only absorbed after direct contact, but that concentrations in the air can lead to the excretion of metabolites in exposed people [ 19 ]. This potential acaricidal effect on ticks that have not come into contact with the hair or the skin has to be kept in mind as the possibility of a certain permethrin concentration in the air can not be eliminated in the chambers.…”
Section: Discussionmentioning
confidence: 99%